PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII6 SMP NEGERI 3 PEKANBARU - Suardiman Suardiman; Zuhri D; Suhermi Suhermi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is the result of learning mathematics of class student VII6 SMP Negeri 16 Pekanbaru which is still under the minimum mastery criteria with a persentage of 10,34 % only 3 students from 29 students who achieve the minimum mastery criteria on the associating the relationship and the area of a rectangle (square, rectangle, length, trapezoid, rhombus, kite) and triangle. The purpose of this research aims to improve the learning process and increase the student’s mathematics learning outcomes through the implementation of Cooperative learning structured approach Numbered Heads Together. This type of research is the Classroom Action Research with two cycle, who conducted in class VII6 SMP Negeri 16 Pekanbaru in the second semester of the 2018/2019 academic year. Research subject as many 29 students, consist of 16 boys and 13 girls. The research instrument consists of learning devices and instrument data collectors. Learning device used is Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. The observation sheet was analyzed whit descriptive qualitative while the test of mathematics learning outcomes was analyzed statistically. Based on deskriptive qualitative analiysis showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test IIare respectively 3 person (10,34 %), 14 person (48,28 %) and 19 person (65,52 %). Results of this research indicates that application of the Cooperative learning structured approach Numbered Heads Together can improve learning process and increase mathematics learning outcomes from the students at class VII6 SMP Negeri 16 Pekanbaru in the second semester academic years 2018/2019.Key Words: Students’ Math Achievement, Cooperative Learning Structural Approach of Numbered Heads Together, Classroom Action Research.